Doenças isquêmicas do coração: mortalidade em nativos e migrantes, São Paulo, 1979-1998 Ischemic heart disease: mortality in natives and migrants, São Paulo, Brazil, 1979-1998 - Luiz Francisco Marcopito (Universidade de São Paulo, 2003)
OBJETIVO: O Estado de São Paulo tem sido pólo de atração de migrantes, tanto estrangeiros como brasileiros, e não se conhece o comportamento da mortalidade por doenças isquêmicas do coração quanto à naturalidade dos falecidos. Assim, realizou-se estudo para identificar diferenciais de mortalidade por doenças isquêmicas do coração em residentes no Estado de São Paulo, segundo sua naturalidade. MÉTODOS: Estudo analítico de série temporal com base em dados secundários. Não foram utilizadas taxas por falta de denominadores, mas sim indicadores não-censitários (mortalidade proporcional, e razão de mortalidade padronizada e ponderada para anos potenciais de vida perdidos antes da idade de 100 anos) e medianas. Tendências temporais foram avaliadas por regressão linear simples. RESULTADOS: Em São Paulo, cerca de 40% dos óbitos por doenças isquêmicas do coração ocorreram em migrantes. A tendência foi negativa nos estrangeiros e positiva nos brasileiros. Os naturais da região Nordeste, que tiveram a maior percentagem de óbitos hospitalares, foram os que apresentaram a pior situação: mortalidade proporcional por doenças isquêmicas do coração estável (embora claramente declinando em todos os outros grupos) e óbitos em idades mais jovens. CONCLUSÕES: A participação de migrantes no total de óbitos por doenças isquêmicas do coração no Estado de São Paulo teve mais destaque nos migrantes brasileiros, sendo que nos nascidos na região Nordeste foi mais destacada do que nos outros grupos de migrantes. OBJECTIVE: The State of São Paulo has been a major center of attraction for foreign and Brazilian migrants since the 19th century. The pattern of mortality due to ischemic heart disease according to place of birth is, however, unknown. Thus, the objective of the study was to identify differences in mortality due to ischemic heart disease among residents of the State of São Paulo according to their place of birth. METHODS: Analytical time series study based on secondary data. Rates were not calculated due to lack of denominators. Instead, non-census indicators (proportional mortality and standardized mortality ratio weighted for years of potential life lost before the age of 100 years) and medians were utilized. Temporal trends were analyzed by means of simple linear regression. RESULTS: In the State of São Paulo, about 40% of deaths due to ischemic heart disease occurred among migrants. The trend was negative for foreigners and positive for Brazilian migrants. Those born in northeastern Brazil, who presented the highest percentage of deaths in hospitals, had the worst performance: their proportional mortality due to ischemic heart disease remained unchanged throughout the study period (while this clearly declined for all other groups) and they died at younger ages. CONCLUSIONS: Migrants' share of total deaths due to ischemic heart disease in the State of São Paulo is very high. While there is a declining trend for foreigners, it is growing among Brazilian migrants. Among the compared groups, mortality due to ischemic heart disease in the State of São Paulo is most prominent for those born in northeastern Brazil.